Teacher-taught Relationship and Academic Achievement of Elementary Schools in Himachal Pradesh - Raj, Hem; Gausiya, Fatma (JOURNAL OF INDIAN EDUCATION, 2018)
An effective teacher-taught relationship is the keystone that allows the other aspect of academics to work well. The teacher-taught relationship serves as an important support for students for achieving better academic performance. This study is designed to assess the teacher-taught relationship and academic achievement of elementary school students. The population of study consisted of three districts of Himachal Pradesh, and a sample of 223 students was drawn from the population using multistage random sampling. A self-developed questionnaire on the teacher-taught relationship was used for collecting data. The questionnaire had 30 items related to various dimensions of the teachertaught relationship. The Pearson Product Moment Correlation and t-test were used for the analysis of data. Research finding shows that there is a significant positive relationship between the teacher-taught relationship and academic achievement. Results also show that there is a significant difference in the teacher-taught relationship on the basis of gender and there exists no significant difference in the teacher-taught relationship in relation to their locale.